Juventudes rurais no Território Integração Norte Pioneiro do Paraná : um estudo dos fatores que interferem em sua decisão de permanecer ou não no meio rural - Morais, Luciana Soares de (2014)
The present discussion about sustainable territorial development requires an understanding of the family farming generally, but specially about the young people that live in rural areas, which are the actors and beneficiaries of this development proposal. In this way, this study tries to understand the reality experienced by youth in the North Pioneer of Paraná as well as the most important factors that motivate young people to continue living in rural areas. Furthermore, this research led us to discuss the importance of the public policies for these groups. Bibliographic and census data, participant observation, interviews and questionnaires were used to achieve our goals. The obtained results permitted us to understand the population dynamics in the municipalities involved in this study, the difficulties, dreams and expectations from the young people about continue or not continue living in rural areas. The key informants were 20 young (men and women) from family farming, including beneficiaries of agrarian reform and agrarian credit, which produce mainly coffee, milk, fruits and vegetables. It was found that the region continues having demographic losses, especially in group from 0 to 24 years old at the same time the 40-year-old-and-older age group has been increasing. It is important to clarify that young women usually leave the rural areas more than young men, what make rural regions like the North Pioneer having more boys than girls (young age - from 15 to 29 years old) in the countryside. The problems faced by family farming over the country like difficult access to land and other resources to produce and low incomes, are also present in this region. Adding to this, there are the problems related to the distance from the city, the lack or poor maintenance of roads, and scarcity of public transportation. There are still special problems such the barriers for access the incomes, devaluation of rural culture by traditional education, gender differences and inequalities, the youth low participation in the decisions, taboos and prejudices related to the rural youth identity, the ignorance and no access to the policies and programs for the family farming. However, since the rural young people are able to own the land, having incomes from the rural property, healthy and sustainable family relationships, access to public policies, sufficient transport and a good education, there is a good chance for them to remain in rural areas. This was the wish of the young rural people we have studied in this research.